2020
DOI: 10.1371/journal.pntd.0008186
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal characteristics of severe fever with thrombocytopenia syndrome and the relationship with meteorological factors from 2011 to 2018 in Zhejiang Province, China

Abstract: Background Zhejiang Province has the fifth-highest incidence of severe fever with thrombocytopenia syndrome (SFTS) in China. While the top four provinces are all located in northern and central China, only Zhejiang Province is located in the Yangtze River Delta region of southeast China. This study was undertaken to identify the epidemiological characteristics of SFTS in Zhejiang from 2011 to 2018. Methods The epidemic data from SFTS cases in Zhejiang Province from January 2011 to December 2018 were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…A national-wide study in China from 2010 to 2018 showed that precipitation had a positive linear association with SFTS occurrence ( 9 ). A nonlinear relationship with monthly mean temperature and precipitation was observed in both a study conducted in Zhejiang Province from 2011 to 2018 ( 20 ) and a national-wide study from 2010 to 2013 ( 21 ). Using ecological niche modes, Sun et al also found that SFTS occurrence had a nonlinear relationship with annual average temperature and precipitation ( 6 ), which is quite consistent with our results.…”
Section: Discussionmentioning
confidence: 96%
“…A national-wide study in China from 2010 to 2018 showed that precipitation had a positive linear association with SFTS occurrence ( 9 ). A nonlinear relationship with monthly mean temperature and precipitation was observed in both a study conducted in Zhejiang Province from 2011 to 2018 ( 20 ) and a national-wide study from 2010 to 2013 ( 21 ). Using ecological niche modes, Sun et al also found that SFTS occurrence had a nonlinear relationship with annual average temperature and precipitation ( 6 ), which is quite consistent with our results.…”
Section: Discussionmentioning
confidence: 96%
“…The main clinical manifestations of SFTS included high fever, gastrointestinal symptoms, and bleeding tendency. Most SFTS patients went through a self-limiting clinical course, but some cases developed serious symptoms (8,(14)(15)(16)(17). Some of the patients (12-30%) may develop thrombocytopenia and leukopenia, and then die due to multiple organ failure (9,14,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Most SFTS patients went through a self-limiting clinical course, but some cases developed serious symptoms (8,(14)(15)(16)(17). Some of the patients (12-30%) may develop thrombocytopenia and leukopenia, and then die due to multiple organ failure (9,14,(17)(18)(19). WHO had listed SFTS as one of the nine infectious diseases on its priority list, due to the increasing number of SFTS cases and its potential threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that meteorological factors influence the risk of tick-borne infections by affecting tick growth dynamics, tick-human interactions, and virus replication 8 . Meteorological factors, including temperature, relative humidity, precipitation, duration of sunshine, and environmental factors, such as land cover and tick density, have been associated with the occurrence of SFTS 9 . The disease usually presents from March to November, peaking between May and July.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported risk factors of SFTS infection analyzed using epidemiological data 9 14 . The risk factors of SFTS cases in China have been analyzed using univariate analysis of epidemiological data 11 , 13 .…”
Section: Introductionmentioning
confidence: 99%